Pakistan's solar mission: Do solar finance and subsidy remove the barriers to solar installations?. (May 2022) - Sher, Ali; Qiu, Yuzhuo
Abstract: This work investigates the impact of solar finance and solar subsidy in removing the barriers to solar installations among households (on-grid and off-grid), the agriculture sector, and small and medium enterprises (SMEs) in Pakistan. This study used step-wise parametric and non-parametric approaches to identify and analyze the nature, grouping, and classification of barriers in the three sectors. First, binary logit regression results confirm that amongst the economic factors, solar finance, solar subsidy, finance lending, solar pay-off periods, consumer wealth, and monthly electricity expenses significantly (positively) related to the solar installations. Second, ranking analysis results reveal that solar finance and solar subsidy significantly lower the barriers to solar installations among the agriculture sector and SMEs as they face only 6 and 8 out of 23 barriers, respectively. Third, the results of factor analysis grouped 16 common critical barriers into five components: 1) economic barriers, 2) green energy policy-related barriers, 3) technological barriers, 4) information and human resource-related barriers, and 5) social barriers. Finally, we used MICMAC analysis to classify critical barriers to each sector based on their driving and dependence power. By doing so, this study comprehensively sheds light on the interrelations of barriers across three sectors and provides practical solutions to meet SDG 7 in developing countries. Graphical abstract: Image 1 Highlights: Current energy policies favor the ongoing addition of coal-fired projects in Pakistan. The influence of solar financing and solar subsidy on solar installations was examined. Ranking, grouping and classification of critical barriers were identified. Both solar financing and solar subsidy positively influences the solar uptake. Most of the barriers to solar installations in the three sectors are interrelated.